Fetal and infant mortality trends according to the avoidability of causes of death and maternal education - Pauline Lorena Kale; Sandra Costa Fonseca; Pedro Willian Marques de Oliveira; Alexandre dos Santos Brito
ABSTRACT: Objective: To estimate trends of fetal (FMR) and neonatal (NMR) mortality rates due to avoidable causes and maternal education in the city of Rio de Janeiro (2000-2018). Methods: Ecological time series study. Mortality and Live Birth Information System Data. The List of Avoidable Causes of Death Due to Interventions of the Brazilian Health System was used for neonatal deaths and an adaptation for fetal deaths, according to maternal education indicators (low <4 and high ≥12, years of study). Joinpoint regression models were used to estimate trends in FMR, based on one thousand births, and NMR, based on one thousand live births. Results: FMR decreased from 11.0 to 9.3% and NMR from 11.3 to 7.8% (2000/2018). In 2006, FMR (10.5%) exceeded NMR (9.0%), remaining higher. From 2000 to 2018, the annual decrease of FMR was 0.8% (2000 to 2018) and of NMR, 3.8% until 2007, decreasing to 1.1% by 2011; from then on, it remained stable. Avoidable causes, especially those reducible by adequate prenatal care, showed higher rates. Both FMR and NMR for low-education women were higher than those for the high-education level, the difference being much more pronounced for FMR, and at the end of the period: low- and high-education FMR were respectively 16.4 and 4.5% (2000) and 48.5 and 3.9% (2018), and for NMR, 18.2 and 6.7% (2000) and 28.4 and 5.0% (2018). Conclusion: The favorable trend of decreasing mortality was not observed for children of mothers with low education, revealing inequalities. The causes were mostly avoidable, being related to prenatal care and childbirth.